2007
DOI: 10.1007/s11606-007-0203-7
|View full text |Cite
|
Sign up to set email alerts
|

Process of Care and Outcomes in Patients with Peripheral Arterial Disease

Abstract: Our data suggest that glucose control is key to reducing the risk for adverse outcomes, particularly limb events in African Americans. Certain process of care measures, as markers of disease severity and disease management, are associated with poor outcomes in patients with PAD. Further work is needed to determine the role of early disease intervention to reduce poor outcomes in patients with PAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…A high rate of amputation has been reported in patients with PVD (20%) [46]. In our series, 28% of patients underwent a below-knee or metatarsal amputation for nonhealing foot wounds.…”
Section: Discussionmentioning
confidence: 59%
“…A high rate of amputation has been reported in patients with PVD (20%) [46]. In our series, 28% of patients underwent a below-knee or metatarsal amputation for nonhealing foot wounds.…”
Section: Discussionmentioning
confidence: 59%
“…Poor glycemic control has been associated with higher prevalence of PAD 18 and risk of adverse outcomes, including the need for lower extremity bypass surgery, amputation or death. 19 In addition, poor glycemic control is also associated with worse outcomes following both vascular surgery 20 and endovascular 6,21 procedures. Takahara et al 21 studied 278 patients who underwent balloon angioplasty for CLI and found that diabetes and poor glycemic control was each associated with higher rates of major amputations.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly the case for patients with PAD or polyvascular disease 7 8. To date, the impact of risk-reduction interventions on fatal and non-fatal ischaemic events in outpatients with atherothrombotic syndrome have only been assessed from retrospective surveys in populations of limited size 9 10. The REACH Registry was initiated to evaluate outpatients who would represent the entire spectrum of atherothrombotic clinical syndromes, from the most geographically and ethnically diverse population yet surveyed.…”
mentioning
confidence: 99%